Antimicrobial activities of ethanolic extraction from leaves of medicinal plants (Padmakanya Journal of Science and Technology, 2025)
Medicinal plants, rich in phytochemicals such as glycosides, phenols, tannins, and alkaloids, are highly valued for their therapeutic properties. This study was a cross-sectional descriptive study conducted between December 2023 and March 2024 to explore the antimicrobial properties of plant extracts against different bacterial strains. In this study,400 grams of leaves from each of four different plants samples (Ocimum tenuiflorum- Holy Basil, Artemisia vulgaris- Mugwort, Azadirachta indica- Neem, and Mentha arvensis- Basil) were collected from Thankot, Kathmandu and laboratory processing was done in Microbiology Laboratory of Padmakanya Multiple Campus. All the test bacteria were collected from Central Department of Microbiology, Tribhuvan University. To determine antimicrobial activities, 200gm of each plant leaves were processed for ethanolic extraction (Soxhlet extractor). Phytochemical analysis of glycosides, alkaloid, flavonoids, steroids, saponins, reducing sugar and phenol and tannins of each plant leaves were done. From ethanolic plant extracts, antimicrobial activity was assessed through the Agar Well Diffusion method and Minimum Bactericidal Concentration (MBC) and Minimum Inhibitory Concentration (MIC) were also carried out. In this study, Phytochemical analysis showed seven phytochemical compounds found in all leaf extracts except alkaloid in Mugwort and Basil and reducing sugar in Neem. From ethanol extracts, Mugwort extract showed the greatest inhibition zone (26mm) against Staphylococcus aureus, whereas Holy Basil extracts showed no inhibition zone against any test bacteria. MIC values varied between 12.5 and 50mg/ml, while MBC values fell within the range of 12.5 to 100mg/ml showing extensive antimicrobial efficacy. This result indicated that ethanol extract of the medicinal plants was effective against test bacteria. Thus, ethanol extracts have potential for developing targeted antimicrobial drugs.